The Implementation of Kurikulum Merdeka in Indonesia Early Childhood Education (PAUD): A Literature Review - Tupalessy, Pricilia (Huele: Journal of Applied Linguistics, Literature and Culture, 2024)
This research explores the implementation of the Merdeka curriculum in early childhood education (PAUD) in Indonesia, which aims to promote holistic development by fostering creativity, critical thinking, and independence. Using a qualitative literature review, this research analyzes existing studies to evaluate the effectiveness, challenges, and impact of the curriculum. Findings show that the curriculum improves learning outcomes, especially in language and social skills, through flexible and adaptive teaching methods. However, challenges such as inadequate teacher training, resistance to change, and unequal access to technology hinder its implementation. This study recommends comprehensive teacher training, clear communication of the curriculum's benefits, and continuous evaluation to overcome these challenges and improve the quality of early childhood education in Indonesia.